Bahasa Indonesia Bahasa Indonesia - Wisoedhanie Widi A (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2015)
Activities to lossing weight sometimes cause obsessive efforts.Yogaexercisesis able for the diet programbecause it encourages participants to resist excessive appetite when stressed. It also resisit someone’sappetite because they will aware notto eat too much. The purpose of this study is to determine whether thereis any relationship between knowledge aboutyogaexercisesfor women related to weight loss and also theirinterest to do so. The research design is a correlation and sample selectedusing accidental samplingtechnique with questionnaires and checklist instruments. The presented of data results with narrative. Theresults were calculated using Spearman correlation test with the significance result is (0,015) < ? (0,05). Sothe conclusion is that there is a relationship between knowledge about senam yoga to lossing weight with aninterest to do so for women. Based on the results of the study, suggestions for the research place is to spreadthe knowledge of participants in the gymnasiumby giving the information about senam yoga to lossingweigh through posters, distribution of brochures, and others. Keywords: Knowledge,Adolescent Girl, Interests,Yoga Exercises